IMPROVING ORGANIZATIONAL AND ECONOMIC MECHANISMS FOR ENHANCING ENERGY EFFICIENCY IN GREENHOUSE FARMING IN UZBEKISTAN (Irrigation and Melioration, 2026)
This study examines the improvement of organizational and economic mechanisms forenhancing energy efficiency in greenhouse farming in Uzbekistan. In recent years, rapid technologicaldevelopment, climate change, and the growing need for sustainable resource management havemade energy efficiency a strategic priority in both developed and developing economies. Theagricultural sector, particularly greenhouse farming, is characterized by high energy consumptiondue to the intensive use of heating, cooling, irrigation, and lighting systems. Therefore, the efficientuse of energy resources has become an important issue for ensuring economic sustainability andcompetitiveness in the sector. The research analyzes the current state of greenhouse farming inUzbekistan, trends in energy consumption, and the impact of energy use ontheeconomicperformanceof greenhouse enterprises. Special attention is given to the role of modern energy-saving technologies,effective management practices, economic incentives, and institutional support in improving energyefficiency. Based on the findings, scientifically grounded recommendations are developed to improveorganizational and economic mechanisms aimed at reducing production costs, increasing productivity,and ensuring sustainable development of greenhouse farming. The results of the study can contributeto strengthening the competitiveness and long-term sustainability of greenhouse enterprises inUzbekistan.